Genotype–phenotype correlations within the Geodermatophilaceae - Montero-Calasanz, Maria del Carmen; Yaramis, Adnan; Rohde, Manfred; Schumann, Peter; Klenk, Hans-Peter; Meier-Kolthoff, Jan P. (Frontiers in Microbiology, 2022)
The integration of genomic information into microbial systematics along with physiological and chemotaxonomic parameters provides for a reliable classification of prokaryotes. In silico analysis of chemotaxonomic traits is now being introduced to replace characteristics traditionally determined in the laboratory with the dual goal of both increasing the speed of the description of taxa and the accuracy and consistency of taxonomic reports. Genomics has already successfully been applied in the taxonomic rearrangement of Geodermatophilaceae (Actinomycetota) but in the light of new genomic data the taxonomy of the family needs to be revisited. In conjunction with the taxonomic characterisation of four strains phylogenetically located within the family, we conducted a phylogenetic analysis of the whole proteomes of the sequenced type strains and established genotype-phenotype correlations for traits related to chemotaxonomy, cell morphology and metabolism. Results indicated that the four isolates under study represent four novel species within the genus Blastococcus. Additionally, the genera Blastococcus, Geodermatophilus and Modestobacter were shown to be paraphyletic. Consequently, the new genera Trujillonella, Pleomorpha and Goekera were proposed within the Geodermatophilaceae and Blastococcus endophyticus was reclassified as Trujillonella endophytica comb. nov., Geodermatophilus daqingensis as Pleomorpha daqingensis comb. nov. and Modestobacter deserti as Goekera deserti comb. nov. Accordingly, we also proposed emended descriptions of Blastococcus aggregatus, Blastococcus jejuensis, Blastococcus saxobsidens and Blastococcus xanthilyniticus. In silico chemotaxonomic results were overall consistent with wet-lab results. Even though in silico discriminatory levels varied depending on the respective chemotaxonomic trait, this approach is promising for effectively replacing and/or complementing chemotaxonomic analyses at taxonomic ranks above the species level. Finally, interesting but previously overlooked insights regarding morphology and ecology were revealed by the presence of a repertoire of genes related to flagellum synthesis, chemotaxis, spore production and pilus assembly in all representatives of the family. A rich carbon metabolism including four different CO2 fixation pathways and a battery of enzymes able to degrade complex carbohydrates were also identified in Blastococcus genomes.